2000
DOI: 10.1152/ajpheart.2000.279.4.h1819
|View full text |Cite
|
Sign up to set email alerts
|

Role of pertussis toxin-sensitive G protein in metabolic vasodilation of coronary microcirculation

Abstract: We have previously demonstrated that pertussis toxin (PTX)-sensitive G protein (G(PTX)) plays a major role in coronary microvascular vasomotion during hypoperfusion. We aimed to elucidate the role of G(PTX) during increasing metabolic demand. In 18 mongrel dogs, coronary arteriolar diameters were measured by fluorescence microangiography using a floating objective. Myocardial oxygen consumption (MVO(2)) was increased by rapid left atrial pacing. In six dogs, PTX (300 ng/ml) was superfused onto the heart surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…The magnitude of the microvascular dilation to the tachypacing was consistent with previous in vivo observations for the size class of microvessels we used (Ϸ200 m). 21 All of these data support the concept that H 2 O 2 released from beating myocardium is a physiological mediator of metabolic coronary microvascular dilation. However, the possibility that H 2 O 2 produced in the vascular endothelium of the beating heart takes part in the DV dilation during tachypacing cannot be ruled out because earlier studies showed that the increased shear stress stimulates H 2 O 2 production from the vascular endothelium.…”
Section: H 2 O 2 As a Vasoactive Mediator For Metabolic Dilationsupporting
confidence: 53%
See 1 more Smart Citation
“…The magnitude of the microvascular dilation to the tachypacing was consistent with previous in vivo observations for the size class of microvessels we used (Ϸ200 m). 21 All of these data support the concept that H 2 O 2 released from beating myocardium is a physiological mediator of metabolic coronary microvascular dilation. However, the possibility that H 2 O 2 produced in the vascular endothelium of the beating heart takes part in the DV dilation during tachypacing cannot be ruled out because earlier studies showed that the increased shear stress stimulates H 2 O 2 production from the vascular endothelium.…”
Section: H 2 O 2 As a Vasoactive Mediator For Metabolic Dilationsupporting
confidence: 53%
“…21 It is possible that H 2 O 2 activates a signaling pathway which involves G PTX , although how H 2 O 2 links to G PTX is not clear at this point. There is a report that H 2 O 2 acutely upregulates sphingosine-1-phosphate receptors, which activate G PTX .…”
Section: H 2 O 2 As a Vasoactive Mediator For Metabolic Dilationmentioning
confidence: 99%
“…Microscopes and fluorescent imaging systems used were previously described. 23,24 Briefly, fluorescent NO images were obtained from microscope (model ECLIPSE E600, Nikon) equipped with ϫ20 (for HMVECs) or ϫ60 (for TRLEC-03) objective. Excitation light was passed though a 495-nm filter, and emitted light was passed through a 510-nm filter.…”
Section: Measurement Of No Production In Ecsmentioning
confidence: 99%
“…4,5,13,14 Briefly, the dogs were anesthetized and ventilated. A thoracotomy was performed, and the pericardium was cut to expose the heart surface.…”
Section: Beating-heart Preparationmentioning
confidence: 99%
“…3 Previous in vivo studies have shown that G PTX proteins are critical in the microvascular control during autoregulation and metabolic stimulation. 4,5 Hypercholesterolemia is one of the most important coronary risk factors. Although morphological changes like plaque formation take place only in conduit vessels, various functional changes are known to extend to the coronary microvessels.…”
mentioning
confidence: 99%